1-Octadecanol@hierarchical porous polymer composite as a novel shape-stability phase change material for latent heat thermal energy storage. (1st February 2017) - Tang, Jia; Yang, Mu; Yu, Fang; Chen, Xingyu; Tan, Li; Wang, Ge
Graphical abstract: Schematic illustration of the prepared procedure of 1-octadecanol@HPP ssPCM. Highlights: A hierarchical porous polymer (HPP) with high porosity (91.9%) was synthesized. The HPP shows pressure-dependent elastic deformation behavior for ssPCMs. The interaction in HPP induces the stability of the β phase of 1-octadecanol. The HPP reduce the extent of the supercooling of 1-octadecanol (37%) effectively. The ssPCMs have high adsorption of 1-octadecanol and high energy storage density. Abstract: A hierarchical porous polymer (HPP), which was prepared by the imine condensation between pararosaniline base and 1, 4-phthalaldehyde, has been used as the supporting material for novel shape-stability phase change materials (ssPCMs). With high porosity (91.9%), the hierarchical pores in the HPP supply sufficient space to adsorb 1-octadecanol, which is restricted in pores by the weak interactions such as hydrogen bonding, surface tension and capillary force in the interfacial region. The HPP exhibits high adsorption of 1-octadecanol (75 wt%) in the ssPCMs, the relative enthalpy of which is up to 169.2 J/g. The solid 13 C NMR spectra and XRD results show that the hydrogen bonding interaction between 1-octadecanol and the HPP in the interfacial region increases the rotational and translational disorder of the 1-octadecanol, and induces the stability of the β phase, effectively reducing the extent of the supercooling of the 1-octadecanol (up to 37%). With its pressure-dependent elastic deformation behavior, the HPP can be adaptable along well with the phase transition of 1-octadecanol, which is of benefit to the crystallinities of 1-octadecanol and the shape stability of the composite PCMs. Thermal cycling and DSC results also confirm the high shape-stability and thermal stability of the ssPCMs.